RETROSPECTIVE ANALYSIS OF VR TECHNOLOGIES AND THEIR IMPLEMENTATION IN EDUCATION - Голуб, Татьяна (Modern engineering and innovative technologies, 2019)
The article is devoted to the study of virtual reality technologies and devices development, as well as to the overview of modern applications used in the educational sphere. The retrospective and historical analysis of the ideas connected to virtual real